2015
DOI: 10.1353/sgo.2015.0015
|View full text |Cite
|
Sign up to set email alerts
|

Regional Income Convergence in Appalachia: Exploring the Factors of Regional Economic Growth in a Transitioning Economy

Abstract: La teoría de convergencia, derivada de la teoría neoclásica de crecimiento, sugiere que las diferencias regionales de salario disminuirán con el tiempo. Estudiada en una variedad de marcos, hay evidencia de que la convergencia ocurre, aunque condicionada por la capacidad económica regional y su participación en la más amplia economía neoclásica. Dentro de los Estados Unidos, la evidencia de convergencia está presente a niveles nacionales y subnacionales. De interés particular en este proceso es la Appalachia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…This result is consistent with the findings of Santopietro (2002), who found that boom cycles associated with extractive industries can lead to unpredictable results in a convergence model. Over time, these outlier effects can lessen as rural, extractive economies diversify and become more strongly integrated in the national economy, as James and James (2015) noted in the case of central Appalachia. Therefore, these outliers need to be contextualized as a very time-specific result, and subject to temporal model volatility as noted by Barro and Sala-I-Martin (2004).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result is consistent with the findings of Santopietro (2002), who found that boom cycles associated with extractive industries can lead to unpredictable results in a convergence model. Over time, these outlier effects can lessen as rural, extractive economies diversify and become more strongly integrated in the national economy, as James and James (2015) noted in the case of central Appalachia. Therefore, these outliers need to be contextualized as a very time-specific result, and subject to temporal model volatility as noted by Barro and Sala-I-Martin (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Industry-specific conditioning variables, drawn from the Minnesota Population Center, are typical of those found in other convergence studies. These specializations are typically expressed as either the percentage of employment in a sector (P. Johnson and Takeyama 2001;Connaughton and Madsen 2004;Higgins, Levy, and Young 2006) or location quotients (James and Campbell 2014;James and James, 2015). Here, they are expressed as the natural log transform of location quotients.…”
Section: Study Area and Model Specificationmentioning
confidence: 99%
See 3 more Smart Citations